Preparing Preservice Teacher for ALL Learners: A Book Critique on Gifted Education and Gifted Students - David S Wolff (The Advocate, 2023)
If is often said that undergraduate coursework in gifted education is a paragraph or chapter in a book. Without specific coursework regarding gifted education and gifted learners, preservice teachers are partially equipped to meet the diverse learning needs in today’s classrooms. This article provides a review of Gifted Education and Gifted Students: A Guide for Inservice and Preservice Teachers by Margot and Melin (2020) as a recommended primer for preservice teachers to gain basic knowledge and understanding of who gifted learners are and how to provided appropriate services for them.
Keywords: gifted education; gifted and talented; gifted learners; preservice teachers; teacher education